Assessment of the attitudes of milk producers in relations to the sale conditions by applying Conjoint analyses - Ostojić Aleksandar; Milunović Darko; Vaško Željko (Agroznanje, 2011)
A conjoint analysis is an exploratory multivariate analysis that is used for modeling decision-making process of potential customers, and about buying a product or service. This analysis is increasingly used for market research purposes. The most common use is through these methods to explore personal attitudes of consumers and other groups of respondents defined by characteristics of the studied phenomena with the aim of finding the optimal combination of these attributes based on the ranking of a combination of predefined responses. The paper presents the results of research of attitudes of milk producers for four conditions of their sales - size of sales price, maturity, distance from milk collection point and mandatory milk quality control. Attitudes were obtained by surveying 20 milk producers, members of the Association of agricultural producers in Siprage (Kotor Varos) in January 2011. By analyzing the received responses and applying methodology of conjoint analyses, it has been determined that milk producers are most sensitive on price of the milk collection price, giving the greatest importance to that. Thereafter, but significantly less important, is the distance from milk collection point, payment terms and (none)existence of mandatory milk quality control.